Effect on the Gastrointestinal Absorption of Drugs from Different Classes in the Biopharmaceutics Classification System, When Treating with Liraglutide - Malm-Erjefält, Monika; Ekblom, Marianne; Vouis, Jan; Zdravkovic, Milan; Lennernäs, Hans (Molecular pharmaceutics, 2015)
Like other GLP-1 receptor agonists used for treatment of type 2 diabetes, liraglutide delays gastric emptying. In this clinical absorption study, the primary objective was to investigate the effect of liraglutide (at steady state) on the rate and/or extent of gastrointestinal (GI) absorption of concomitantly orally taken drugs from three classes of the Biopharmaceutics Classification System (BCS). To provide a general prediction on liraglutide drug–drug absorption interaction, single-dose pharmacokinetics of drugs representing BCS classes II (low solubility–high permeability; atorvastatin 40 mg and griseofulvin 500 mg), III (high solubility–low permeability; lisinopril 20 mg), and IV (low solubility–low permeability; digoxin 1 mg) were studied in healthy subjects at steady state of liraglutide 1.8 mg, or placebo, in a two-period crossover design. With liraglutide, the oral drugs atorvastatin, lisinopril, and digoxin showed delayed t max (by ≤2 h) and did not meet the criterion for bioequivalence for C max (reduced C max by 27–38%); griseofulvin had similar t max and 37% increased C max. Although the prespecified bioequivalence criterion was not met by all drugs, the overall plasma exposure (AUC) of griseofulvin, atorvastatin, lisinopril, and digoxin only exhibited minor changes and was not considered to be of clinical relevance.